Phytochemical Screening and Acute Toxicity Test of Caulerpa lentillifera J. Agardh Infusion Extract on Mice (Mus musculus L.) - Adiyanti, Sekar; Phabiola, Trisna Agung; Sutari, Ni Wayan Sri (Central Laboratory for Genetic Resource and Molecular Biology, Faculty of Agriculture, Udayana University, 2024)
Caulerpa lentillifera has ingredients that are beneficial for health, such as anti-cancer, antioxidant, anti-diabetic, and immunostimulatory effects. This study was aimed to determine the content of phytochemical compounds and the LD50 acute toxicity dose of C. lentillifera infusion extracts on mice for their utilization as food or medicine. The phytochemical screening was done with a qualitative method. Twenty-five mice have been used for the acute toxicity test and divided into five groups of treatment (Control; 375 mg/kg BW; 750 mg/kg BW; 1.500 mg/kg BW; 3.000 mg/kg BW C. lentillifera infusion extracts orally). Symptoms of toxicity and mortality were observed 24 hours after treatment, and body weight was observed for seven days. The phytochemical screening result showed that the C. lentillifera infusion extracts contained alkaloids, saponins, and tannins. Acute toxicity tests showed no mortality in all treatment groups. Thus, the LD50 value could not be obtained and was classified as non-toxic.